Counter-Terrorism as a Public Policy: theoretical Insights and Broader Reflections on the State of Counter-Terrorism Research - Renard, Thomas (Perspectives on terrorism, 2021)
In spite of the growing amount of literature published on terrorism over the past 20 years, counter-terrorism is rarely considered as a subject of research by itself. Empirical or data-driven research on counter-terrorism policy is relatively rare, and theoretical approaches are even scarcer. This article first reflects on the seeming absence of ‘counter-terrorism studies’ (contrasting with the thriving ‘terrorism studies’). Then, it suggests studying counter-terrorism policymaking through the lens of public policy theory. This approach offers innovative insights to our understanding of counter-terrorism and opens new horizons for the development of a theory of counter-terrorism policymaking.